Is it wrong to try to pick Up girls in a dungeon? : Vol. 8 - Omori, Fujino; Kunieda (Yen Press, 2017)
Bell's adventures in the dungeon continue in this eighth installment of the massively popular manga adaptation of the original light novel series!